Perceived precarious life: a SEM model for re-dimensioning of precarious work and its impact on mental health - Llosa, José Antonio; Agulló-Tomás, Esteban; Menéndez-Espina, Sara; Rivero-Díaz, María Luz (Frontiers in Public Health, 2024)
Introduction Precarious work is one of the most studied concepts related to work, and its effects have been analyzed in relation to variables such as mental health and wellbeing. However, there is a tendency to atomise the analysis of precarious work, without understanding that people's working life is intertwined with other areas of their life. Objective Faced with this situation, this paper presents the concept of perceived precarious life, which is aligned with contemporary models of social inclusion and exclusion. Thus, perceived precarious life comprises variables of labor precariousness, social support and hopelessness in the family economic situation. Methods To test this idea, a structural equation model (SEM) is presented, which tests the structure of the construct of perceived precarious life by relating it to mental health and coping strategies. Results After testing the fit of the model in both men and women, a SEM path analysis is designed between the variables, observing that perceived precarious life has an effect on mental health (β = 0.635, p < 0.01). This relationship is mediated by unproductive coping strategies (β = 0.142, p < 0.01). Conclusion This model exposes a broad and integrated conceptualization of precariousness, combining aspects of work, relationships and hopelessness, which allows for an understanding of the integral experience of precariousness.